Autumn bird migration phenology: A potpourri of wind, precipitation and temperature effects. (27th July 2019) - Haest, Birgen; Hüppop, Ommo; van de Pol, Martijn; Bairlein, Franz
Abstract: Climate change has caused a clear and univocal trend towards advancement in spring phenology. Changes in autumn phenology are much more diverse, with advancement, delays, and 'no change' all occurring frequently. For migratory birds, patterns in autumn migration phenology trends have been identified based on ecological and life‐history traits. Explaining interspecific variation has nevertheless been challenging, and the underlying mechanisms have remained elusive. Radar studies on non‐species‐specific autumn migration intensity have repeatedly suggested that there are strong links with weather. In long‐term species‐specific studies, the variance in autumn migration phenology explained by weather has, nevertheless, been rather low, or a relationship was even lacking entirely. We performed a spatially explicit time window analysis of weather effects on mean autumn passage of four trans‐Saharan and six intra‐European passerines to gain insights into this apparent contradiction. We analysed data from standardized daily captures at the Heligoland island constant‐effort site (Germany), in combination with gridded daily temperature, precipitation and wind data over a 55‐year period (1960–2014), across northern Europe. Weather variables at the breeding and stopover grounds explained up to 80% of the species‐specific interannual variability in autumn passage. Overall, wind conditions were most important. For intra‐European migrants, wind was even twice as important as either temperature or precipitation, and the pattern also held in terms of relative contributions of each climate variable to the temporal trends in autumn phenology. For the trans‐Saharan migrants, however, the pattern of relative trend contributions was completely reversed. Temperature and precipitation had strong trend contributions, while wind conditions had only a minor impact because they did not show any strong temporal trends. As such, understanding species‐specific effects of climate on autumn phenology not only provides unique insights into each species' ecology but also how these effects shape the observed interspecific heterogeneity in autumn phenological trends. Abstract : Explaining interspecific variation in autumn bird migration phenology trends has been challenging. We performed a spatially explicit time window analysis of weather effects on mean autumn passage of four trans‐Saharan and six intra‐European passerines at the island of Heligoland (Germany) over a 55‐year period (1960–2014). Weather variables at the breeding and stopover grounds explained up to 80% of the species‐specific interannual variability in autumn passage. Overall, wind conditions were most important, but the climatic contributions to the temporal trend in autumn migration phenology consisted of a potpourri of wind, precipitation and temperature effects.